2011
DOI: 10.1088/0953-8984/23/36/365501
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and luminescence mechanisms in ZnMoO4crystals

Abstract: Calculations of the band structure, partial densities of states and optical spectra of permittivity, reflectivity and absorption of perfect ZnMoO 4 crystal were performed using the full-potential linear-augmented-plane-wave method. It is shown that the calculated reflectivity spectra reproduce the main features of corresponding experimental spectra in the fundamental absorption region. The bandgap value of ZnMoO 4 is estimated as E g = 4.3 eV. Peculiarities of luminescence excitation spectra corrected for near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
34
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 43 publications
12
34
0
2
Order By: Relevance
“…The optical bandgap value of the undoped ZnMoO 4 nanoplates can be calculated to be 3.70 eV. This optically derived bandgap value agrees roughly with the theoretically calculated bandgap value of 3.79 eV [9]. A quite similar bandgap value (3.72 eV) is derived for Eu 3+ doped ZnMoO 4 nanoplates.…”
Section: Eusupporting
confidence: 84%
See 3 more Smart Citations
“…The optical bandgap value of the undoped ZnMoO 4 nanoplates can be calculated to be 3.70 eV. This optically derived bandgap value agrees roughly with the theoretically calculated bandgap value of 3.79 eV [9]. A quite similar bandgap value (3.72 eV) is derived for Eu 3+ doped ZnMoO 4 nanoplates.…”
Section: Eusupporting
confidence: 84%
“…In the case of ZnMoO 4 , the band-edge excitonic recombination can be excluded since the bandgap of ZnMoO 4 is about 4 eV [9,10]. Consequently, the defects in ZnMoO 4 should be the candidate of the broadband PL centered at about 550 nm.…”
Section: Eumentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, this synthesis method enables the attainment of pure molybdate at low temperatures (120 o C -160 o C) in micro and nanoscale with excellent photoluminescence (PL) properties [37][38][39][40][41]. From a theoretical perspective, only one recent research [42] has been reported in the literature which shows band structure calculations and partial densities of states for the triclinic structure of α-ZnMoO 4 crystals using the full-potential linear-augmented-plane-wave method.…”
Section: Introductionmentioning
confidence: 99%